The isoelectric point of proteins influences their translocation to the extrahaustorial matrix of the barley powdery mildew fungus. (14th August 2019) - Smigielski, Lara; Aguilar, Geziel B.; Kwaaitaal, Mark; Zhang, Wen‐Jing; Thordal‐Christensen, Hans
Abstract: Many biotrophic fungal plant pathogens develop feeding structures, haustoria, inside living plant cells, which are essential for their success. Extrahaustorial membranes (EHMs) surround haustoria and delimit the extrahaustorial matrices (EHMxs). Little is known about transport mechanisms across EHMs and what properties proteins and nutrients need in order to cross these membranes. To investigate this further, we expressed fluorescent proteins in the cytosol of infected barley leaf epidermal cells after particle bombardment and investigated properties that influenced their localisation in the powdery mildew EHMx. We showed that this translocation is favoured by a neutral isoelectric point (pI) between 6.0 and 8.4. However, for proteins larger than 50 kDa, pI alone does not explain their localisation, hinting towards a more complex interplay between pI, size, and sequence properties. We discuss the possibility that an EHM translocon is involved in protein uptake into the EHMx.